Islet-1 specifies the identity of hypothalamic melanocortin neurons and is critical for normal food intake and adiposity in adulthood - Nasif, Sofia (2015)
Food intake and body weight regulation depend on proper expression of the proopiomelanocortin gene (Pomc) in a group of neurons located in the mediobasal hypothalamus of all vertebrates. These neurons release POMC-encoded melanocortins, which are potent anorexigenic neuropeptides, and their absence from mice or humans leads to hyperphagia and severe obesity. Although the pathophysiology of hypothalamic POMC neurons is well understood, the genetic program that establishes the neuronal melanocortinergic phenotype and maintains a fully functional neuronal POMC phenotype throughout adulthood remains unknown. Here, we report that the early expression of the LIM-homeodomain transcription factor Islet 1 (ISL1) in the developing hypothalamus promotes the terminal differentiation of melanocortinergic neurons and is essential for hypothalamic Pomc expression since its initial onset and throughout the entire lifetime. We detected ISL1 in the prospective hypothalamus just before the onset of Pomc expression and, from then on, Pomc and Isl1 coexpress. ISL1 binds in vitro and in vivo to critical homeodomain binding DNA motifs present in the neuronal Pomc enhancers nPE1 and nPE2, and mutations of these sites completely disrupt the ability of these enhancers to drive reporter gene expression to hypothalamic POMC neurons in transgenic mice and zebrafish. ISL1 is necessary for hypothalamic Pomc expression during mouse and zebrafish embryogenesis. Furthermore, conditional Isl1 inactivation from POMC neurons impairs Pomc expression, leading to hyperphagia and obesity. Our results demonstrate that ISL1 specifies the identity of hypothalamic melanocortin neurons and is required for melanocortin-induced satiety and normal adiposity throughout the entire lifespan